Increased platelet oxidative metabolism, blood oxidative stress and neopterin levels after ultra-endurance exercise - de Lucas, R. D.; Caputo, F.; de Souza, K. M.; Sigwalt, A. R.; Ghisoni, K.; Lock Silveira, P.; Remor, A. P.; da Luz Scheffer, D.; Antonacci Guglielmo, L. G.; Latini, A. (Journal of Sports Sciences, 2014)
The purpose of the present investigation was to identify muscle damage, inflammatory response and oxidative stress blood markers in athletes undertaking the ultra-endurance MultiSport Brazil race. Eleven well-trained male athletes (34.3 ± 3.1 years, 74.0 ± 7.6 kg; 172.2 ± 5.1 cm) participated in the study and performed the race, which consisted of about 90 km of alternating off-road running, mountain biking and kayaking. Twelve hours before and up to 15 minutes after the race a 10 mL blood sample was drawn in order to measure the following parameters: lactate dehydrogenase and creatine kinase activities, lipid peroxidation, catalase activity, protein carbonylation, respiratory chain complexes I, II and IV activities, oxygen consumption and neopterin concentrations. After the race, plasma lactate dehydrogenase and creatine kinase activities were significantly increased. Erythrocyte TBA-RS levels and plasma protein carbonylation were markedly augmented in post-race samples. Additionally, mitochondrial complex II activity and oxygen consumption in post-race platelet-rich plasma were also increased. These altered biochemical parameters were accompanied by increased plasma neopterin levels. The ultra-endurance event provoked systemic inflammation (increased neopterin) accompanied by marked oxidative stress, likely by increasing oxidative metabolism (increased oxidative mitochondrial function). This might be advantageous during prolonged exercise, mainly for efficient substrate oxidation at the mitochondrial level, even when tissue damage is induced.